In the era of the valve-in-valve: is transcatheter aortic valve implantation (TAVI) in sutureless valves feasible? - Di Eusanio, Marco; Saia, Francesco; Pellicciari, Giovanni; Phan, Kevin; Ferlito, Marinella; Dall’Ara, Gianni; Di Bartolomeo, Roberto; Marzocchi, Antonio (Annals of Cardiothoracic Surgery, 2015)
Sutureless aortic valve implantation has emerged as an innovative alternative for treatment of aortic stenosis. By avoiding the placement of sutures, this approach aims to improve surgical outcomes by facilitating less traumatic minimally invasive approaches and reducing cross-clamp and cardiopulmonary bypass duration. However, the absence of sutures may have detrimental effects after sutureless interventions, including paravalvular leakages, valve dislocation, and stent-infolding. Transcatheter aortic valve-in-valve implantation (A-ViV) is emerging as a valuable procedure in patients with dysfunctioning biological aortic valves who are deemed inoperable with conventional surgery. Here we present the first-in-man case of trans-femoral implant of a balloon expandable aortic valve in a leaking sutureless self-expandable valve.